Epigenetic regulation of Parkinson’s disease risk variant GPNMB cg17274742 methylation by sex and exercise from Taiwan Biobank - Chen, Yen-Chung; Liaw, Yi-Chia; Nfor, Oswald Ndi; Hsiao, Chih-Hsuan; Zhong, Ji-Han; Wu, Shey-Lin; Liaw, Yung-Po (Frontiers in Aging Neuroscience, 2023)
Background Parkinson’s disease (PD) is a complex neurodegenerative disease with an elusive etiology that involves the interaction between genetic, behavioral, and environmental factors. Recently, epigenetic modifications, particularly DNA methylation, have been recognized to play an important role in the onset of PD. Glycoprotein non-metastatic melanoma protein B (GPNMB), a type I transmembrane protein crucial for immune cell activation and maturation, has emerged as a potential biomarker for the risk of PD. This research aims to investigate the influence of exercise and gender on the regulation of methylation levels of GPNMB cg17274742 in individuals. Methods We analyze data from 2,474 participants in the Taiwan Biobank, collected from 2008 and 2016. Methylation levels at the GPNMB cg17274742 CpG site were measured using Illumina Infinium MethylationEPIC beads. After excluding individuals with incomplete data or missing information on possible risk factors, our final analysis included 1,442 participants. We used multiple linear regression models to assess the association between sex and exercise with adjusted levels of GPNMB cg17274742 for age, BMI, smoking, drinking, coffee consumption, serum uric acid levels, and hypertension. Results Our results demonstrated that exercise significantly influenced the methylation levels of GPNMB cg17274742 in males (β = −0.00242; p = 0.0026), but not in females (β = −0.00002362; p = 0.9785). Furthermore, male participants who exercised showed significantly lower levels of methylation compared to the reference groups of the female and non-exercising reference groups (β = −0.00357; p = 0.0079). The effect of the interaction between gender and exercise on the methylation of GPNMB cg17274742 was statistically significant (p = 0.0078). Conclusion This study suggests that gender and exercise can modulate GPNMB cg17274742, with hypomethylation observed in exercise men. More research is needed to understand the underlying mechanisms and implications of these epigenetic changes in the context of risk and prevention strategies.